Impact of blood pressure control during pregnancy on long-term maternal cardiovascular health – secondary analysis of a follow-up study 15 years post preeclampsia (PAVA study) - Charlotte Lößner; Anne Loheit; Anna Multhaup; Laura Bäz; Thomas Lehmann; Yvonne Heimann; Ekkehard Schleußner; Marcus Franz; Tanja Groten (PLoS ONE, 2026)
Background Within the PAVA study, we investigated placenta-associated vascular aging in women 15 years after pregnancies complicated by preeclampsia and/or fetal growth restriction. During these pregnancies, blood pressure values >140/90 mmHg were considered to require treatment. Following evidence demonstrating improved pregnancy outcomes with tighter blood pressure control, updated German and international guidelines (International Society for the Study of Hypertension in Pregnancy, ISSHP) now recommend target values below 135/85 mmHg. To evaluate whether blood pressure levels during pregnancy are associated with long-term maternal cardiovascular health, we analyzed the impact of blood pressure control during pregnancy on cardiovascular risk profiles obtained in the PAVA follow-up study. Methods Between August 2019 and December 2022, 53 women were examined an average of 15 years after experiencing preeclampsia and/or fetal growth restriction. At the study visit, baseline data were collected, and a comprehensive clinical and functional assessment was performed. This analysis compared 35 women who were hypertensive at follow-up (blood pressure ≥140/90 mmHg and/or antihypertensive medication) with 18 normotensive participants (blood pressure <140/90 mmHg and no antihypertensive medication). Data on blood pressure levels during pregnancy were collected retrospectively from medical records. Results Blood pressure data during pregnancy were available for the second trimester in 15 women who later developed hypertension and 4 who remained normotensive, and for the third trimester in 19 and 14 participants, respectively. Data from the first trimester were not available. In group comparisons, systolic blood pressure in the second trimester and diastolic blood pressure in the third trimester were significantly higher in women who were hypertensive at follow-up (155 vs. 140 mmHg, p = 0.027; 96 vs. 87 mmHg, p = 0.026). In adjusted analyses, no statistically significant associations were observed; however, effect estimates suggested a potential association between blood pressure control during pregnancy and lower odds of later arterial hypertension (OR 0.22, 95% CI 0.03–1.53) and concentric remodeling (OR 0.37, 95% CI 0.03–4.29). Conclusions These findings suggest that blood pressure levels during pregnancy may be associated with long-term maternal cardiovascular health. However, given the limited sample size and exploratory nature of the analysis, these results should be interpreted with caution and require confirmation in larger prospective studies.